Golgi protein 73 versus alpha-fetoprotein as a biomarker for hepatocellular carcinoma: a diagnostic meta- analysis - Zhou, Ying (BioMed Central, 2012)
BACKGROUNDS: There have been conflicting reports about serum golgi protein 73 (GP73) as one of the most promising serum markers for the diagnosis of hepatocellular carcinoma (HCC). This study was to make a systematic review about the diagnostic accuracy of serum GP73 versus alpha-fetoprotein (AFP) for HCC. METHODS: After a systematic review of related studies, sensitivity, specificity and other measures about the accuracy of serum GP73 and AFP in the diagnosis of HCC were pooled using random-effects models. Summary receiver operating characteristic curve analysis was used to summarize the overall test performance. RESULTS: Eight studies were included in our meta-analysis. The summary estimates for serum GP73 and AFP in diagnosing HCC in the studies included were as follows: sensitivity, 76% (95% confidence interval (CI) 51-91%) vs. 70% (47-86%); specificity, 86% (95%CI 65-95%) vs. 89% (69-96%); diagnostic odds ratio (DOR), 18.59 (95%CI 5.33-64.91) vs. 18.00(9.41-34.46); and area under sROC, 0.88 (95%CI 0.77-0.99) vs. 0.86 (95%CI 0.84-0.87). CONCLUSIONS: The current evidence indicates that serum GP73 has a comparable accuracy to AFP for the diagnosis of HCC, while the value of serum GP73 in combination with AFP for HCC detection deserves further investigation.